(3CNdGb GdUMaj GdegfjIs - (3YWG Gddg(B, (3GdQeMjfs ((3YeGf(B:s (3eDSSI GdhQGb ddfTQ hGdJhRjY(B,s, 2023)
(3GdaUd GdGhd (B: (3GNdGb GdUMaj GdegfjI HhUagG YdeG heSGdI YedjI GNdGbjG ,GOHjG,eYfhjG GdaUd GdKGfj (B: (3ef GdeVMc GdMOjK Yf Yde GdGNdGb aj eLGd GdegfI GdGcKQ JfGaSjI GdaUd GdKGdK (B: (3Gjf jYjT hYj GdLeGYI GdaUd GdQGHY (B: (3GdJUhQGJ GdGNdGbjI (B- (3GdegfjI GdeQTOI dSdhc GdUMaj GdaUd GdNGeS (B: (3MJi eHGODc JhLO HhaQI GdaUd GdSGOS (B: (3GdeYGjjQ eKdgG ceKd GdQbGHI GdaUd GdSGHY (B: (3GdfhGMj GdefgjI hGdbGfhfjI ddGef GdGYdGej hGdSjchGhLj aj hSGFd GdGYdGe GdLeGgjQj GdaUd GdKGef (B: (3GdJbOe GdJcfhdhLj aj eLGd hSGFd GdGYdGe GdLeGgjQj ef ehGbY GdGef GdGYdGej GdSjchdhLj hGdHjFj hGdHjhdhLj GdaUd GdJGSY (B: (3GdJfXje GdbGfhfj dGef GWaGd GdYGde GdYQHj GdGYdGej GdaUd GdYGTQ (B: (3GdJLQHI GdNGQLjI ddJfXje GdbGfhfj dMeGjI GdGef GdGYdGej YfO JMbjb GdHK GdGPGYj hGdJdaRjhfj GdaUd GdMGOj YTQ (B: (3GdGJUGd GdLeGgjQj heTcdI GdYfas
(3GdeQGLY U(B.327 (3GdedGMb U(B.225 (3GdeUWdMGJ GdEYdGejI U(B.337s
Keywords: (3GdEYdGe GdLeGgjQj (B- (3GdUMGaI s; (3GdUMGaI (B- (3GdCNdGb GdegfjI s